The Effect of Leg Exercise on Changes in Blood Sugar Levels in the Elderly Patients with Type II Diabetes Mellitus at the Ciracas District Health Center - Riyanto, Akbar; Susanti, Fajar; Ifadah, Erlin; Hadisaputra, Sugeng (Journal of Ageing And Family, 2021)
AbstractIncreasing prevalence of type 2 Diabetes Mellitus in developed and developing countries is a health problem. Therefore, type 2 Diabetes Mellitus can be prevented by regular exercise, healthy and regular life. The purpose of this study was to determine the effectiveness of foot exercise on changes in blood sugar levels in elderly people with type 2 diabetes mellitus at the Ciracas District Health Center. This type of research is experimental with one group pre-post test design. The population in this study were 36 elderly people with type 2 Diabetes Mellitus in the Ciracas District Health Center. The sample in this study were 18 elderly with type 2 diabetes mellitus in Ciracas District Health Center. The sampling technique used was convenience sampling. Methods of data collection using an observation sheet before and after being given foot exercises. The statistical test used in this study is the paired T test. The results showed that there was no change in blood sugar levels before and after doing foot exercises, the statistical test results obtained a p value of 0.870, which means 0.870> 0.05, it can be concluded that there is no significant effect between foot exercise and changes in blood sugar levels in elderly patients. Type II diabetes mellitus at the Ciracas Subdistrict Health Center. The absence of any effect of foot exercises on changes in blood sugar levels in the elderly could be due to incomplete exercise, therefore foot exercise training to change blood sugar levels must be done in the elderly. Keywords : Foot exercise, Blood Sugar Levels, DM type 2